Se préparer pour « piloter son clown » à l’hôpital - Claire Bodelet (Revue d'anthropologie des connaissances)
This article focuses on the preparatory work of a group of artists known as the “hospital clowns”. Based on an ethnographic fieldwork in two hospitals with the clowns of a French ONG called Le Rire Médecin, it shows how this work follows a process that is not limited to the formalized time of the preparation of the clowns in the changing rooms but also continues during the shows, at different times of the day and in interactions with the public. Indeed, at the hospital, clown performances are not written in advance but improvised on the spot, and “piloted” in duo with partners who don't always know each other in advance. This work configuration raises practical issues, to which part of the solutions lies in taking action.